Timidez e exclusão-inclusão escolar: um estudo sobre identidade - Vieira, Mariana Batista (2010)
The recent study had as goal understand how is the constitution of the identity from a person who express shyness and the situations of exclusion-inclusion that this person may come to suffer at school. The theory of identity from Antonio da Costa Ciampa was used as the theoretical basis. Accordingly to Ciampa (2007), identity is metamorphosis, and metamorphosis is life, the idea of moviment and continuous transformations are part of a identity process . The shyness is defined by Wallon ([1938] 1985) as one emotion and accordingly to the materialism dialetic, theoretical basis of Ciampa (2007) and Wallon ([1938] 1985) can be understood that shyness is a human condition that can be developed in social relationships. Two participants that experienced situations involving shyness on their lives and on the school environment were chosen. Using a qualitative approach, life s narrative, autobiographical memories and non-direct and reflexives interviews were used as resource. The participant´s narratives were analyzed separately then the differences and resembles of both lives were exposed. The data demonstrate that the participants grew as shy persons on the familiar and social ´s relationships and both suffered of exclusion on the school through the visibility-invisibility and on the second participant´s narrative are situations of bullying. Can be noted that are moments that the participants remains the same or they can get over the shyness towards an emancipatory transformation